Whole person healthcare as social and environmental justice: new research directions toward a paradigmatic integration of an ecological whole system medicine framework - Agarwal, Vinita (Frontiers in Communication, 2024)
With increasing recognition of the interdependencies of human and planetary health, calls for a socially and environmentally just framework of health have centered on whole person healthcare (WPHC) approaches. This perspective piece proposes an argument for broadening the definition of human health from WPHC to one that is guided by the philosophical orientation of traditional whole system medicine (WSM) approaches, undergirded by the values of social and environmental justice, and supported by the practices of an allopathic-integrative medicine-based WPHC framework. This piece presents opportunities for praxis offered by a WSM–WPHC framework to address global inequity, environmental disparities, and sustainability challenges. An ecological WSM–WPHC framework envisages social and environmental justice in material and discursive ways by foregrounding environmental planetary ecological consciousness as constitutive of human consciousness and biopsychosocial composition. It argues for structural support through formalized programmatic pathways targeting funding opportunities and mechanisms that invite investigations addressing epistemic challenges of expanding definitions of evidence constituting basic science knowledge domains beyond mechanistic, causal, and formative paradigms. Furthermore, it calls for innovative research directions examining the integration and validation of evidence-based approaches incorporating the ontologically diverse and epistemically distinct ontological orientation of WSM and clinical approaches. A WSM–WPHC framework that positions human health within the parameters of social and environmental justice principles envisions the material enactment of the practice of health and medicine as a universal planetary value.